Multilateral Retributivism: Justifying Change - Eva, Richard R. (Stance: an international undergraduate philosophy journal, 2015)
In this paper I argue for a theory of punishment I call Multilateral Retributivism. Typically retributive notions of justice are unilateral: focused on one person’s desert. I argue that our notions of desert are multilateral: multiple people are owed when a moral crime is committed. I argue that the purpose of punishment is communication with the end-goal of reconciling the offender to society. This leads me to conclude that the death penalty and life without parole are unjustified because they necessarily cut communication short.